Upaya Guru untuk Meningkatkan Keterampilan Berbicara Siswa dengan Menggunakan Metode Role-Playing dalam Pengajaran Bahasa Indonesia - Annisa Annisa; Desty Endrawati Subroto; Ananda Rizky Amalia; Nasyril Fathani; Neneng Mawar Muhlisoh (Institut Nalanda, 2025)
Simply put, this study was inspired by the phenomenon of students being passive and talking about their findings or opinions. Many students are unable to express themselves, uncomfortable, unconfident, and unsure of what they want to say when they are instructed to participate in class activities. This shows that students' speaking experiences are on average quite negative, which affects their speaking ability. In addition, the teaching methods applied by teachers are less than optimal in fostering the development of students' skills. This study aims to evaluate the strategies applied by teachers in helping students improve their role-playing skills when learning Indonesian. This study applies a qualitative descriptive approach with data collection methods through observation, analysis, and documentation. The findings of the study revealed that the role-playing method helps students understand various difficult concepts through discussions with friends. This method motivates active student involvement and group cooperation, resulting in a collaborative learning atmosphere in the classroom. Speaking skills are defined as the ability to convey ideas, thoughts, or ideas through speech so that they can be understood by others. Activities that support the development of these skills include interaction and communication with people around students.